Pengembangan Tungku Briket Batubara Skala Rumah Tangga - Tamrin Tamrin (agriTECH, 2010)
Improving of a coal briquette stove is required in the context of energy diversification for strengthening national energy security. The policy of kerosene conversion to LPG is a short term policy and needs other source of energy alternative.  In idealized sense, all potentials should be used for household cooking, not always depending on a particular energy source. Purpose of this research was to improve a household coal briquette stove to increase stove efficiency and ease in ceasing the ember. Design criteria of the coal briquette stove were based on heat transfer from the burning coal to the heated object, ease in ceasing the ember, and facilitating the exhausting smoke from the kitchen room. Performance test to the designed stove was conducted on analyses of temperature at the bottom of a pan versus time during the firing, heat efficiency, and the time of ceasing ember. The results showed that the cooking temperature (>180 oC) was reached after 35-65 minutes. The cooking temperature lasted for 4 hours, heat efficiency of 25.5 % was about optimum, and the time of ember ceasing was 19-33 minutes.ABSTRAKPengembangan tungku briket batubara sangat diperlukan dalam diversifikasi pemakaian energi bahan bakar agar ketahanan energi nasional  menjadi kuat.  Kebijakan pengalihan bahan bakar minyak tanah ke elpiji merupakan ke- bijakan jangka pendek dan perlu energi alternatif lainnya  Idealnya  semua potensi yang ada dapat digunakan untuk memasak, tidak harus bergantung pada energi tertentu.  Tujuan penelitian ini adalah untuk mengembangkan tungku briket batubara skala rumah tangga untuk meningkatkan efiseinsi dan memudahkan pematian bara api. Tungku briket batubara dibuat didasarkan pada sistem pindah panas dari bara briket ke objek yang dipanaskan, memudahkan pe- matian bara api briket batubara dan menyalurkan asap dari ruang pembakaran keluar dari ruang dapur. Pengujian dilakukan untuk mengetahui perubahan suhu dasar panci selama pembakaran, untuk mendapatkan efisiensi tungku dan lama waktu mematikan bara api briket. Hasil pengamatan terhadap tungku hasil pengembangan menunjukkan bahwa suhu layak memasak (>180 oC) dicapai selama 35-65 menit, lama suhu layak memasak sekitar 4 jam. Efisiensi maksimum tungku adalah 25,5 % dan lama pematian bara api  adalah 19-33 menit.